Additional structured physical activity does not improve walking in older people (>60years) undergoing inpatient rehabilitation: a randomised trial - Said, Catherine M; Morris, Meg E; McGinley, Jennifer L; Szoeke, Cassandra; Workman, Barbara; Liew, Danny; Hill, Keith D; Woodward, Michael; Wittwer, Joanne E; Churilov, Leonid; Danoudis, Mary; Bernhardt, Julie (Journal of physiotherapy, 2018)
Among older people receiving inpatient rehabilitation, does additional supervised physical activity lead to faster self-selected gait speed at discharge? Does additional supervised physical activity lead to better mobility, function and quality of life at discharge and 6 months following discharge? Multi-centre, parallel-group, randomised controlled trial with concealed allocation, assessor blinding, and intention-to-treat analysis. Older people (age>60years) from two Australian hospitals undergoing rehabilitation to improve mobility. Participants received multidisciplinary care, including physiotherapy. During hospital rehabilitation, the experimental group (n=99) spent additional time daily performing physical activities that emphasised upright mobility tasks; the control group (n=99) spent equal time participating in social activities. Self-selected gait speed was the primary outcome at discharge and a secondary outcome at the 6-month follow-up. Timed Up and Go, De Morton Mobility Index, Functional Independence Measure and quality of life were secondary outcomes at discharge and tertiary outcomes at the 6-month follow-up. The experimental group received a median of 20 additional minutes per day (IQR 15.0 to 22.5) of upright activities for a median of 16.5days (IQR 10.0 to 25.0). Gait speed did not differ between groups at discharge. Mean gait speed was 0.51m/s (SD 0.29) in the experimental group and 0.56m/s (SD 0.28) in the control group (effect size −0.06m/s, 95% CI −0.12 to 0.01, p=0.096). No significant differences were detected in other secondary measures. While substantial gains in mobility were achieved by older people receiving inpatient rehabilitation, additional physical activity sessions did not lead to better walking outcomes at discharge or 6 months. ACTRN12613000884707. [Said CM, Morris ME, McGinley JL, Szoeke C, Workman B, Liew D, Hill KD, Woodward M, Wittwer JE, Churilov L, Danoudis M, Bernhardt J (2018) Additional structured physical activity does not improve walking in older people (> 60 years) undergoing inpatient rehabilitation: a randomised trial. Journal of Physiotherapy 64: 237–244]